Pembinaan dan Pengembangan Minat Baca di Perpustakaan SMP Negeri 3 Tembilahan Hulu - Maimunah; Rahmawati; Mirnawati; Normalinda, Siti; Rahmi, Gustina (Universitas Islam Indragiri, 2023)
Interest in reading has a big influence on student’s succes so it needs to be instilled from an early age. Libraries play a role in fostering students interest in reading through groviding a collection of services and activities. The aim of this research. Is to increase and provide guidance on the reading interest of students at SMP Negeri 3 Tembilahan Hulu which apperas to be very low. This research is qualitative research using descriptive methods. Collecting data by making direct observations and systematic recording of the symptoms or phenomena being investigated. The author uses this method by directiy observing the condition of the school library and the number of students who visit to read books. The results of this research show that there is a lack of interest in reading among students, the weekly literacy schedule that is determined is sometimes not implemented, as well as the lack of effectiveness of literacy activities in the library of SMP Negeri 3 Tembilahan Hulu. Limited library collections, a reading room that is not too large, lack of awareness. Students to read and non-permanent library professionals. In increasing students’ interest in reading, librarian teachers use several strategies, namely making a weekly literacy activities, making and filling out a literacy attendance list, filling in a list of borrowing and returning library books, and arranging library books.